Ethnobotanical survey of medicinal plants used by the Mamanwa tribe of Surigao del Norte and Agusan del Norte, Mindanao, Philippines - Olga Nuneza; BIVERLY RODRIGUEZ; Juliet Grace Nasiad (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Nuneza OM, Rodriguez BC, Nasiad JGM. 2021. Ethnobotanical survey of medicinal plants used by the Mamanwa tribe of Surigao del Norte and Agusan del Norte, Mindanao, Philippines. Biodiversitas 22: 3284-3296. Traditional knowledge on medicinal plants plays an important role in public healthcare and development of drugs. In the Philippines, studies on ethnomedicinal plants have increased throughout the years. However, documentation on the ethnobotanical knowledge in Mindanao is few and mostly focused on other well-known tribes. This ethnobotanical study was carried out to document medicinal plants used by the Mamanwas tribe in ten Indigenous Cultural Communities (ICCs) of Surigao del Norte and Agusan del Norte, Philippines. Ethnomedicinal information on the plant parts used, different modes of preparation, and mode of utilization was gathered from 143 local informants through informal interviews and semi-structured questionnaires. Seventy-eight plant species under 70 genera and 42 families were documented to treat various ailments in their communities. Family Asteraceae held the dominance with ten species that were reported to have medicinal uses. Out of the 78 species, trees constituted the largest proportion with 32 plant species that cover 41%. In terms of plant parts used, leaves are frequently used constituting 46%. As to mode of preparation, decoction (40%) ranked the highest followed by poultice (18%) and heating over fire (14%). Documentation of the valuable ethnomedicinal knowledge will help preserve the vanishing tradition of cultural communities in terms of medicinal plant utilization.